Effect of Compensation, Motivation, and Ability to Work Achievement at Waropko District Office, BovenDigoel, Papua - Susana Marcel Tuwok; Syamsu Alam; Maat Pono (Magister Management, Hasanuddin University, 2020)
This research aims for the purpose of this research that is to know and analyze the influence of the compensation of employees ' work performance in the Waropko district office of BovenDigoel Regency. To know and analyze the influence of the motivation to work performance of employees at the Waropko District office of BovenDigoel Regency. To find out and analyze the influence of the ability to work achievements in the Waropko district office of BovenDigoel County. To know and analyze the influence of the compensation, motivation, and ability to work achievement of employees in the district office Waropko County BovenDigoel. Methods used are quantitative research methods. In this study, a population of 92 people, using a sample of 48 people. Using multiple linear regressions. Data analysis techniques using SPSS 21.The results of the study showed a partially partial compensation variable to the employee's work performance at the Waropko District office of BovenDigoel, a partially partial motivation variable to the employee's work achievement at the Waropko District office of the BovenDigoel District, a partially half-beheaded The variable compensation, motivation, and ability together (simultaneous) significant influence on the work achievement of officers in the district office Waropko BovenDigoel